Filsafat Ilmu dalam Perspektif Islam: Integrasi Wahyu dan Akal dalam Pengembangan Ilmu Pengetahuan - Sanra Mahenra Hatoguan; Efendi; Fuji Arifzapni; Ardiansyah Rambe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The philosophy of science plays a crucial role in understanding how knowledge develops and is applied, particularly within the Islamic sciences. This article examines the relationship between the philosophy of science and the various disciplines of Islamic scholarship, as well as how historical factors and religious norms influence the development of knowledge. The history of science in the Islamic tradition reveals the interaction between divine revelation, human reason, and social needs, all of which contribute to the formation of knowledge. The philosophy of science provides a framework for understanding scientific foundations while preserving the religious values inherent in Islamic teachings. The integration of the Islamic sciences with other scientific fields is essential for expanding our understanding of the world. Furthermore, this article explains that knowledge in the Islamic tradition constitutes an interconnected system in which rational, ethical, and spiritual dimensions operate harmoniously. Through historical and normative approaches, the study demonstrates that science in Islam represents a holistic unity that remains relevant to contemporary scientific advancements.